2018
DOI: 10.4253/wjge.v10.i2.56
|View full text |Cite
|
Sign up to set email alerts
|

Utility of endoscopic ultrasound and endoscopy in diagnosis and management of hepatocellular carcinoma and its complications: What does endoscopic ultrasonography offer above and beyond conventional cross-sectional imaging?

Abstract: Hepatocellular carcinoma constitutes over 90% of the primary liver tumors, the rest being cholangiocarcinoma. It has an insidious presentation, which is responsible for the delayed presentation. Hence, the management strategy relies on screening to diagnose it an early stage for curative resection and/or treatment with local ablative techniques or chemotherapy. However, even with different screening programs, more than 60% of tumors are still detected at an advanced stage, leading to an unchanged mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 123 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…After NAC, the regression of tumor cells mainly manifests as necrosis and fibrosis of the lesions (32,33). Conventional ultrasound cannot accurately distinguish between necrosis, fibrous hyperplasia and residual cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…After NAC, the regression of tumor cells mainly manifests as necrosis and fibrosis of the lesions (32,33). Conventional ultrasound cannot accurately distinguish between necrosis, fibrous hyperplasia and residual cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, liver cancer remains one of the worst malignant tumors[ 3 ]. Despite this, early detection, early diagnosis, and early surgical treatment are still the keys to improved clinical outcomes in liver cancer treatment[ 4 ]. In recent years, with the advancement of diagnosis and treatment techniques for liver cancer, many patients have been diagnosed with liver cancer at early stages, and the detected tumors have been surgically removed, yielding a timely and effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Having a spike in AFP of >20,000 with consistently negative imaging prompted us to probe further with EUS. EUS is superior to CT in detecting small hepatic lesions, with a sensitivity of 100% compared with 71% of CT. 14 Several studies have postulated the benefit of EUS with FNA in detecting HCC. A retrospective study by Awad et al 15 on preoperative evaluation of hepatic lesions using EUS showed that in all 14 patients who underwent EUS and CT, EUS detected additional hepatic lesions in 28% of the patients.…”
Section: Discussionmentioning
confidence: 99%